2013
DOI: 10.1055/s-0033-1340316
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Direct Nucleophilic Substitution of Allylic Alcohols through SN1-Type Reactions

Abstract: Direct nucleophilic substitution reactions of allylic alcohols are environmentally friendly, since they generate only water as a byproduct, allowing access to new allylic compounds. This reaction has, thus, attracted the interest of the chemical community and several strategies have been developed for its successful accomplishment. This review gathers the latest advances in this methodology involving S N 1-type reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(42 citation statements)
references
References 19 publications
1
41
0
Order By: Relevance
“…In contrast to bidentate ligands, monodentate phosphines and 1,3-bis(2,6-diisopropyl)imidazol-2-ylidene (IPr) were not effective for the present system ( Table 2, entries 9-13). We next screened solvents, that is, 1,4-dioxane, 1,2-dichloroethane, hexane, and toluene ( Table 2, entries [14][15][16][17], revealing that acetonitrile gave the best result, probably because it facilitates the replacemento f1 ,5-cyclooctadiene on an ickel center. [15] Consequently,w eselected dppf as the best ligand and acetonitrile as the bests olvent.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to bidentate ligands, monodentate phosphines and 1,3-bis(2,6-diisopropyl)imidazol-2-ylidene (IPr) were not effective for the present system ( Table 2, entries 9-13). We next screened solvents, that is, 1,4-dioxane, 1,2-dichloroethane, hexane, and toluene ( Table 2, entries [14][15][16][17], revealing that acetonitrile gave the best result, probably because it facilitates the replacemento f1 ,5-cyclooctadiene on an ickel center. [15] Consequently,w eselected dppf as the best ligand and acetonitrile as the bests olvent.…”
Section: Resultsmentioning
confidence: 99%
“…One of us previously reported that a Ni 0 ‐diphosphine system acted as a catalyst for the amination of allyl alcohol with diethylamine to prepare allylamines,11 the most versatile organic compounds among allylic‐substituted products 12. Some nonprecious metal complexes also act as catalysts for direct amination of allylic alcohols with electron‐deficient nitrogen nucleophiles through carbocationic intermediates 13. 14…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of Green Chemistry, easily available and cheap alcohols are attractive sources of electrophiles and the only by‐product formed in the reaction of alcohols and thiols is water. Thus, direct nucleophilic substitution reactions of alcohols have gained much attention . Previously, we realized direct synthesis of polysubstituted olefins via construction of C‐C bonds from alcohols or alkenes with alcohols and also developed system for direct amination of alcohols , .…”
Section: Introductionmentioning
confidence: 99%
“…In 2013 Zheng's group developed the method for the direct nucleophilic substitution of propargylic alcohols with various nucleophiles using Amberlite IR-120H resin as the catalyst. 21 The direct nucleophilic substitution of allylic alcohols [22][23][24] through S N 1-type reactions in the presence of Brønsted acid as a catalyst has been reviewed, 25 Table 7. Moreover, the direct nucleophilic S N 1-type reactions of alkynols 26,27 in the presence of Brønsted acid as a catalyst have been reviewed 28 and selected results are shown in Table 8.…”
mentioning
confidence: 99%